2011
DOI: 10.1007/s00520-011-1193-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying determinants of quality of life of children with cancer and childhood cancer survivors: a systematic review

Abstract: Our study has compiled evidence about determinants of QOL for children with cancer and childhood cancer survivors from the existing literature. Future research can build on this evidence base to expand the range of factors studied as most research to date has focused on medical and treatment factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
133
4
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 64 publications
9
133
4
9
Order By: Relevance
“…As according to Bredow and Peterson that quality of life is influenced by individual and environmental variables. 14 Further review articles about the variables that are often studied to determine the quality of life of children who have cancer conducted by Klassen et al reported that some of these are factors when assessing the child's age, age at diagnosis, sex, phase of treatment/chemotherapy, and socioeconomic status. 15 In this study the characteristics of the child in terms of age at assessment gained an average of 6.9 years old and most are in the toddler (1-3 years old children).…”
mentioning
confidence: 99%
“…As according to Bredow and Peterson that quality of life is influenced by individual and environmental variables. 14 Further review articles about the variables that are often studied to determine the quality of life of children who have cancer conducted by Klassen et al reported that some of these are factors when assessing the child's age, age at diagnosis, sex, phase of treatment/chemotherapy, and socioeconomic status. 15 In this study the characteristics of the child in terms of age at assessment gained an average of 6.9 years old and most are in the toddler (1-3 years old children).…”
mentioning
confidence: 99%
“…Improvements in diagnosis and increased survival rates of pediatric illnesses in recent decades have encouraged a growing interest in assessing and improving the quality of life of children (for review, see Klassen, Anthony, Khan, Sung, & Klaassen, 2011). Traditionally, research in the area has focused on the negative consequences of an illness, such as psychological and physical symptoms associated with the course of the disease or applied treatments (Aaronson & Beckman, 1987;Varni et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These factors include demographic, socio-economic status, diagnosis, treatment intensity and time in treatment. [13][14][15] The identification of these factors allowed the development of interventions mediating these factors in children with cancer. 1,14,16 Despite progress in improving HRQOL in children with cancer, most published studies provide incomplete information describing the impact of time and treatment.…”
Section: Health-related Quality Of Life In Children With Cancermentioning
confidence: 99%
“…[13][14][15] The identification of these factors allowed the development of interventions mediating these factors in children with cancer. 1,14,16 Despite progress in improving HRQOL in children with cancer, most published studies provide incomplete information describing the impact of time and treatment. The majority of studies only assess single diagnostic groups of children with cancer, include small sample sizes, utilize a cross sectional design, measure a limited number of treatment factors, which limits the ability to report change in HRQOL over time.…”
Section: Health-related Quality Of Life In Children With Cancermentioning
confidence: 99%
See 1 more Smart Citation